The Androstenedione Roche Elecsys immunoassay has superior comparability to the LC-MS/MS assay than the Siemens Immulite immunoassay - Ruhan Wei; Kathleen Bowers; Grace M. Kroner; Drew Payto; Jessica M. Colón-Franco (Practical Laboratory Medicine, 2022)
Androstenedione (ASD) is a biomarker used in the diagnostic workup of hyperandrogenism, congenital adrenal hyperplasia, premature adrenarche, and polycystic ovary syndrome (PCOS). The Elecsys ASD competitive electrochemiluminescence immunoassay (Roche Diagnostics, Indianapolis, IN) is a new assay recently available in the US. Objective: This study evaluated the analytical and clinical performance of the Elecsys ASD assay. Design & Methods: We evaluated the linearity/analytical measuring range (AMR), precision, and accuracy of the Elecsys ASD assay on the cobas e601 analyzer. ASD was measured in serum/plasma in the Elecsys ASD, Immulite (Siemens Medical Solutions USA, Inc. Malvern, PA), and LC-MS/MS assays. Reference intervals (RI) were evaluated across genders, menopausal status, and in children. Statistical analysis was performed using EP evaluator and R program. Results: The Elecsys ASD assay had a linear response across the AMR. The intra- and inter-assay coefficients of variation at various concentrations were ≤4.5%. The Elecsys ASD assay had a mean difference of −0.04 ng/mL (−1.7%) with the LC-MS/MS assay, whereas the Immulite assay had a mean difference of 1.17 ng/mL (66%) and −1.22 ng/mL (−38%) compared to the LC-MS/MS and Elecsys ASD assays, respectively. The Roche recommended RIs for healthy men (0.280–1.52 ng/mL) and postmenopausal women (0.187–1.07 ng/mL) were successfully verified. The RIs for children were adopted from published data. For pre-menopausal women, a RI of <1.60 ng/mL was established. The ASD concentrations in women with and without PCOS overlapped. Conclusions: The Elecsys ASD assay has superior comparability to the LC-MS/MS assay than the Immulite assay.